Gender Performance Gaps Across Different Assessment Methods and the Underlying Mechanisms: The Case of Incoming Preparation and Test Anxiety - Salehi, Shima; Cotner, Sehoya; Azarin, Samira M.; Carlson, Erin E.; Driessen, Michelle; Ferry, Vivian E.; Harcombe, William; McGaugh, Suzanne; Wassenberg, Deena; Yonas, Azariah; Ballen, Cissy J. (Frontiers in Education, 2019)
A persistent ‘gender penalty’ in exam performance disproportionately impacts women in large introductory science courses, where exam grades generally account for the majority of the students’ assessment of learning. Previous work in introductory biology demonstrates that some social psychological factors may underlie these gender penalties, including test anxiety and interest in course content. In this paper, we examine the extent that gender predicts performance across disciplines, and investigate social psychological factors that mediate performance. We also examine whether a gender penalty persists beyond introductory courses, and can be observed in more advanced upper division science courses. We ran analyses (1) across two colleges at a single institution: the College of Biological Sciences and the College of Science and Engineering (i.e., physics, chemistry, materials science, math); and (2) across introductory lower division courses and advanced upper division courses, or those that require a prerequisite. We affirm that exams have disparate impacts based on student gender at the introductory level, with female students underperforming relative to male students. We did not observe these exam gender penalties in upper division courses, suggesting that women are either being ‘weeded out’ at the introductory level, or ‘warming to’ timed examinations. Additionally, results from mediation analyses show that across disciplines and divisions, for women only, test anxiety negatively influences exam performance.